Sustentabilidade nos quilombos João Surá e Jaó - do Carmo, Maristela Simões [UNESP]; Comitre, Valeria; Borsatto, Ricardo Serra (My University, 2016)
The present paper studied from primary data the level of sustainability in two maroon communities in their economic, ecological and technological dimensions. Data were collected from questionnaires, with closed and open questions, applied to the leaders of the communities studied. The answers were analyzed trough an indicator system based in the MESMIS methodology. The survey results showed that changes in habits that are introjected by the external environment has impacted on production systems and food security of communities. But despite a noticeable cultural erosion process, the communities still use strategies that guarantee autonomy from the external environment.
Sustainability in João Surá and Jáo maroon communities (quilombos)
Keywords: Food security; Sustainability indicators; Traditional communities